A Young Man with Headache & Loss of Vision - Siddqui, Md Mahmudur Rahman; Mahbub, Md Shahriar; Khan, Mohammad Ashik Imran (Journal of Medicine, 2011)
DOI: 10.3329/jom.v12i1.6942 J Medicine 2011; 12 : 97